Integrasi Rasionalitas dan Moralitas dalam Pemikiran Pendidikan Al-Farabi: Relevansinya terhadap Pendidikan Islam Kontemporer - Rubaini Ubay; Ita Tryas Nur Rochbani (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study explores al-Farabi’s educational thought and its relevance to contemporary Islamic education. Al-Farabi views education as a means to achieve human perfection (al-sa’ādah al-quṣwā) through the balanced development of rational, moral, and spiritual faculties. Employing a library research method with content analysis, this study examines primary sources such as Ara’ Ahl al-Madinah al-Fadilah and Kitab al-Tanbih ‘ala Sabil al-Sa’adah, alongside secondary literature discussing al-Farabi’s philosophical and pedagogical ideas. The findings reveal that al-Farabi emphasizes the integration of reason and virtue as the foundation of education, positioning the teacher as both a moral and intellectual guide. His concept of the “Active Intellect” (al-‘aql al-fa’āl) offers an epistemological framework that connects knowledge acquisition with spiritual elevation. These ideas remain highly relevant for modern Islamic education in addressing moral, intellectual, and spiritual challenges in the era of globalization.